2019
DOI: 10.1186/s43055-019-0005-z
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic validity of thoracic ultrasound in the assessment of pulmonary embolism

Abstract: Background: To determine the sensitivity, specificity, positive predictive value, negative predictive value, and diagnostic accuracy of thoracic ultrasound (TUS) in patients with moderate to high clinical suspicion of pulmonary embolism (PE). Twenty-five patients with moderate or high clinical suspicion of PE were enrolled in a prospective study. The patients' ages were 20 to 50 years (mean age = 36 years). They were evaluated by TUS and standard contrast-enhanced CT pulmonary angiography (CTPA). Results: In c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
2
5
0
Order By: Relevance
“…TUS was applied to all patients in this study and high probability for PE was the presence of at least one typical subpleural hypoechoic lesion with or without pleural effusion. TUS was true positive in 24 (24.0%) and false-negative in 2 (2.0%) which is similar to the results published by Baz et al [22] in 2019 that TUS with its high specificity and diagnostic accuracy should be widely performed in AECOPD patients.…”
Section: Discussionsupporting
confidence: 87%
“…TUS was applied to all patients in this study and high probability for PE was the presence of at least one typical subpleural hypoechoic lesion with or without pleural effusion. TUS was true positive in 24 (24.0%) and false-negative in 2 (2.0%) which is similar to the results published by Baz et al [22] in 2019 that TUS with its high specificity and diagnostic accuracy should be widely performed in AECOPD patients.…”
Section: Discussionsupporting
confidence: 87%
“…Our initial systematic search yielded 6378 unique articles. Of these, 93 studies were selected for eligibility through full-text assessment of which 62 studies were finally included 17–78. Six further studies were included by examining the reference list of included publications 79–84…”
Section: Resultsmentioning
confidence: 99%
“…Ultrasound (US) is a routine diagnostic tool in patients with dyspnea and/or chest pain in daily clinical practice, especially in the emergency setting, and the method is also reproducible and radiation-free [ 30 ]. Although not mentioned in the current ESC guidelines, recent studies have confirmed the validity of pulmonary US in patients with PE [ 31 , 32 , 33 , 34 ]. Also, PI can be visualized with the US [ 35 ].…”
Section: Possible Diagnostic Criteriamentioning
confidence: 99%
“…Interestingly, in one study, contrast-enhanced ultrasound was informative for PI diagnosis in patients with PE and negative CTPA [ 38 ]. Despite this promising data, pulmonary US is characterized by some limitations when used alone [ 32 ] as it can miss central lesions and is able to identify the alterations related to the so-called “early infarction” or “pulmonary hemorrhage” on a narrow time frame (a few hours) [ 37 ]. Moreover, this technique is influenced by the examiner, is time-consuming, and requires practice [ 39 ].…”
Section: Possible Diagnostic Criteriamentioning
confidence: 99%